Revitalisasi Pos Kamling Berbasis Komunitas di Masa Pandemi Covid-19 - Pribadi, Slamet (Jurnal Keamanan Nasional, 2020)
The state and society place great hopes on the state apparatus, especially the Indonesian National Army (TNI) and Indonesian National Police (Polri), to prevent the spread of Covid-19. It is also explicitly stated in Government Regulation Number 21 of 2020 concerning Large-Scale Social Restrictions in the Context of Accelerating Handling of Corona Virus Disease 2019 (Covid-19) and Minister of Health Regulation Number 9 of 2020 concerning Guidelines for Large-Scale Social Restrictions in the Context of Accelerating Handling of Coronavirus Virus Disease 2019 (Covid-19). Even though the two institutions are precise andvery strategic, it is necessary to have synergy between the government apparatus and the community in facing the threat of the Covid-19 pandemic. Therefore, this article examines the role of an independent environmental security system (Siskamling) with Poskamling (environmental security post) as a collaborative mechanism for handling pandemics between the government and the community. Moreover, in Indonesia Poskamling and Siskamling are models of community-based security systems that become the insights of the Indonesian archipelago.